2019
DOI: 10.1007/s00705-019-04166-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of a novel recombinant of porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea (PED) is a contagious viral disease in pigs, caused by the coronavirus porcine epidemic diarrhea virus (PEDV). PEDV infection results in significant mortality in piglets in unvaccinated herds. Like many others RNA viruses, PEDV has high evolutionary rate and is prone to genetic mutations. In this study, we analyzed the complete genome sequence of the recently sequenced isolate PEDV/Belgorod/dom/2008. A recombination event in S gene of PEDV/Belgorod/ dom/2008 was detected. Pairwise ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, a recent study showed that two Chinese PDCoV strains respectively, based on a phylogenetic analysis of the S gene (Mai et al, 2018). This finding indicates that recombination between different PDCoV strains might occur in the field, which is indeed worthy of our attention, because this phenomenon has already been confirmed to exist in PEDV (Boniotti et al, 2016;Nefedeva et al, 2019;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent study showed that two Chinese PDCoV strains respectively, based on a phylogenetic analysis of the S gene (Mai et al, 2018). This finding indicates that recombination between different PDCoV strains might occur in the field, which is indeed worthy of our attention, because this phenomenon has already been confirmed to exist in PEDV (Boniotti et al, 2016;Nefedeva et al, 2019;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Recombination events have been reported in animal and human coronaviruses, such as PEDV and severe acute respiratory syndrome (SARS), these viruses have a history of recombination with other lineages of coronavirus [51,52]. Su S et al posit that the large genome and multiple host species were major factors for the high rate of recombination events, which can alter tissue tropism, transmission routes, and host specificity [53].…”
Section: Discussionmentioning
confidence: 99%
“…2016 ; Chen et al. 2017 ; Nefedeva, Titov, and Malogolovkin 2019 ). Here, we report a new high pathogenic recombinant strain, CN/Liaoning25/2018, resulting from the recombination of the S gene from the high pathogenic CN/GDZQ/2014 strain with the remaining genes of the low pathogenic attenuated vaccine SQ2014 strain ( Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…There are two patterns of recombination within and between different virus subgroups/species. In one pattern, PEDV recombines with other coronaviruses, such as the chimeric virus SeCoV/GER/L00930/2012 the Italy/213306/2009 strain or PEDV/Belgorod/dom/2008 ( Nefedeva, Titov, and Malogolovkin 2019 ), a recombinant form of PEDV and porcine transmissible gastroenteritis virus (TGEV). The other recombination pattern involves the recombination of PEDV with different PEDV strains, including recombination of different pathogenic strains from the same or different subgroups.…”
Section: Introductionmentioning
confidence: 99%